Corticospinal tract diffusion properties and robotic visually guided reaching in children with hemiparetic cerebral palsy. Issue 3 (29th November 2017) - Kuczynski, Andrea M.; Dukelow, Sean P.; Hodge, Jacquie A.; Carlson, Helen L.; Lebel, Catherine; Semrau, Jennifer A.; Kirton, Adam
Abstract: Perinatal stroke is the leading cause of hemiparetic cerebral palsy (CP), resulting in life‐long disability. In this study, we examined the relationship between robotic upper extremity motor impairment and corticospinal tract (CST) diffusion properties. Thirty‐three children with unilateral perinatal ischemic stroke (17 arterial, 16 venous) and hemiparesis were recruited from a population‐based research cohort. Bilateral CSTs were defined using diffusion tensor imaging (DTI) and four diffusion metrics were quantified: fractional anisotropy (FA), mean (MD), radial (RD), and axial (AD) diffusivities. Participants completed a visually guided reaching task using the KINARM robot to define 10 movement parameters including movement time and maximum speed. Twenty‐six typically developing children underwent the same evaluations. Partial correlations assessed the relationship between robotic reaching and CST diffusion parameters. All diffusion properties of the lesioned CST differed from controls in the arterial group, whereas only FA was reduced in the venous group. Non‐lesioned CST diffusion measures were similar between stroke groups and controls. Both stroke groups demonstrated impaired reaching performance. Multiple reaching parameters of the affected limb correlated with lesioned CST diffusion properties. Lower FA and higher MD were associated with greater movement time. Few correlations were observed between non‐lesioned CST diffusion and unaffected limb function though FA was associated with reaction time ( R  = −0.39, p  < .01). Diffusion properties of the lesioned CST are altered after perinatal stroke, the degree of which correlates with specific elements of visually guided reaching performance, suggesting specific relevance of CST structural connectivity to clinical motor function in hemiparetic children.